Exercise and cognitive performance in chronic fatigue syndrome - Cook, D. B.; Nagelkirk, P. R.; Peckerman, A.; Poluri, A.; Mores, J.; Natelson, B. H. (Medicine & Science in Sports & Exercise, 2005)
Abstract: Purpose: To determine the effect of submaximal steady-state exercise on cognitive performance in patients with chronic fatigue syndrome (CFS) alone, CFS with comorbid fibromyalgia FM (CFS+FM), and sedentary healthy controls (CON).